2008
DOI: 10.1002/pola.22689
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic graft modification of a commercial crystalline polyolefin

Abstract: Hydroxy-functionalized isotactic poly(1-butene) was synthesized using transition metal-catalyzed regioselective CÀ ÀH borylation at the side chain of the commercial polyolefin and subsequent oxidation of the boronic ester functionality. Functionalization up to $ 19 mol % of the termini of the ethyl side chain occurred without significant side reactions that could alter the polymer chain length. Esterification of the hydroxy group in the polymer with 2-bromoisobutyl bromide generated a side chain-functionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
(84 reference statements)
0
25
0
2
Order By: Relevance
“…This is in contrast to the findings of Bae et al, who reported a decrease in both the T m and X c upon chemical hydrolysis of PB-g-PtBA materials. [13] We also observed a decrease in the melting transition and a more pronounced decrease in crystallinity for the AA grafts prepared via the thermal treatment. This is illustrated by comparison of entries AA3 and AA4, which reveals that the thermolysis product has a slightly lower X c (13 vs. 16%), and a significantly lower T m (93 vs. 125 8C).…”
Section: Synthesis and Characterization Of Acrylic Acid Graft Copolymersmentioning
confidence: 54%
See 3 more Smart Citations
“…This is in contrast to the findings of Bae et al, who reported a decrease in both the T m and X c upon chemical hydrolysis of PB-g-PtBA materials. [13] We also observed a decrease in the melting transition and a more pronounced decrease in crystallinity for the AA grafts prepared via the thermal treatment. This is illustrated by comparison of entries AA3 and AA4, which reveals that the thermolysis product has a slightly lower X c (13 vs. 16%), and a significantly lower T m (93 vs. 125 8C).…”
Section: Synthesis and Characterization Of Acrylic Acid Graft Copolymersmentioning
confidence: 54%
“…13 C solid-state NMR spectra were obtained using a Bruker Avance 300 MHz spectrometer operating at 50.3 MHz for 13 C. A 4 mm double-tuned magic-angle spinning (MAS) probe head from Bruker was used, along with a 4 mm ZrO 2 rotor and a kel-F cap. The sample was spun at 10 kHz.…”
Section: Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…They found that polypropylene can be selectively functionalized at the pendant methyl groups with B 2 pin 2 (Pin ¼ pinacolato) in the presence of Cp*Rh(C 6 Me 6 ) as the catalyst (2, Scheme 1b) [21]. Similar methods were developed for the functionalization of LLDPE and for isotactic poly(1-butene) (up to 19% borylation) [22,23]. Bae and coworkers investigated the borylation of atactic, isotactic, and syndiotactic polystyrene in the presence of an Ir catalyst (e.g., [IrCl(COD)] 2 /dtbpy) and achieved high degrees of functionalization (3, up to 42% borylation) [24].…”
Section: Polymer Modification Reactions On Polyolefinsmentioning
confidence: 87%